2019
DOI: 10.1186/s13014-019-1235-y
|View full text |Cite
|
Sign up to set email alerts
|

3-weekly or weekly cisplatin concurrently with radiotherapy for patients with squamous cell carcinoma of the head and neck – a multicentre, retrospective analysis

Abstract: BackgroundConcurrent chemoradiotherapy with cisplatin is standard for patients (pts) with loco-regionally advanced squamous cell carcinoma of the head and neck (LA-SCCHN) and for patients with resected SCCHN with high-risk features. The standard regimen includes 3-weekly cisplatin, but weekly regimens are often used to lower toxicity. Reaching a cumulative dose of ≥200 mg/m2 cisplatin was shown being associated with improved outcome. We herein investigated cumulative dose reached and toxicities between the 3-w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 45 publications
2
32
1
1
Order By: Relevance
“…With the limitation of the small number of patients in this study and without any difference between MMC-based and platin-based chemotherapy for all endpoints, MMC/5-FU could at least be considered as an alternative therapeutic option. However, in the published literature cisplatin is reported as the standard treatment for a simultaneous monotherapy with the strongest effect [17, 18]. The clinical results of our ARO-analog subgroup and the ARO 95–06 trial were comparable with a 5-year PFS of 30.4% versus 29.3% and a 5-year OS of 36.4% versus 28.6%.…”
Section: Discussionmentioning
confidence: 54%
“…With the limitation of the small number of patients in this study and without any difference between MMC-based and platin-based chemotherapy for all endpoints, MMC/5-FU could at least be considered as an alternative therapeutic option. However, in the published literature cisplatin is reported as the standard treatment for a simultaneous monotherapy with the strongest effect [17, 18]. The clinical results of our ARO-analog subgroup and the ARO 95–06 trial were comparable with a 5-year PFS of 30.4% versus 29.3% and a 5-year OS of 36.4% versus 28.6%.…”
Section: Discussionmentioning
confidence: 54%
“…Similar to our study, the rate of PEG dependence was not different (63.7% in B-CP and 56.1% in the W-CP). 15 Another randomized study reported by Tsan et al including 50 patients (26 in B-CP and 24 in W-CP group) showed a higher rate of mucositis (75% vs 38.5%, P = .01) and grade 4 toxicity (25% vs 0%, P = .02) in patients treated with B-CP. 16 On the other hand, there are studies that did not show a significant toxicity difference in patients with B-CP and W-CP.…”
Section: Discussionmentioning
confidence: 91%
“…In a latest study, only 47% of the patients were able to receive dose >200 mg/m 2 with weekly cisplatin while 76% of patients received this dose with three weekly cisplatin. 13 This could be due to flexibility of decision of chemotherapy which is to be done at only two time points. Also, it can be hypothesized that most of the patients will have recovered from high dose toxicities of chemotherapy.…”
Section: Discussionmentioning
confidence: 99%